Evaluasi Indeks Konsumsi Energi Listrik di Rumah Sakit Daerah Umum R.A. Kartini Jepara - Kurniawan, Samuel; Safrizal, Safrizal; Arifin, Zaenal (Mestro: Jurnal Teknik Mesin dan Elektro, 2025)
This study aims to evaluate the electrical energy consumption index at the R.A. Kartini Regional General Hospital (RSUD Jepara). Electrical energy efficiency is a crucial aspect in the management of modern health facilities, especially in efforts to reduce operational costs and environmental impacts. Hospitals as facilities that operate 24 hours have high energy consumption, especially for medical equipment, air conditioning systems, and lighting. This study uses a quantitative descriptive analysis method by processing electricity consumption data in 2018 obtained from official hospital documents. The results showed that the total installed power at the R.A. Kartini Regional General Hospital Jepara reached 1,410,005 VA, with the largest distribution of energy use in medical devices (51.5%), air conditioning systems (38.7%), and mechanical equipment (20.7%) The hospital's Energy Consumption Index (IKE) was calculated at 146 kWh/m²/year, which is included in the "fairly efficient" category according to Indonesian national standards (180-280 kWh/m²/year). However, there is still room for increased efficiency, especially in air conditioning and lighting systems. The research findings show that the application of inverter technology in the AC system, replacing conventional lamps with LEDs, and optimizing the use of mechanical equipment can result in energy savings of up to 25-30%. This study recommends the implementation of a comprehensive energy management system, including periodic energy audits, increasing equipment efficiency, and educating staff about energy-saving practices. With these steps, RSUD R.A. Kartini Jepara can achieve the IKE target of 102-110 kWh/m²/year, approaching international best practices. In addition, this study also provides an important contribution to energy conservation efforts in the health sector, especially in supporting national and global policies on energy sustainability